Enhancing transplant quality by optimizing LED light spectrum to advance post-transplant runner plant propagation in strawberry - Chen, Jian; Ji, Fang; Gao, Rongwei; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2025)
Light quality is a critical determinant in controlling the quality of strawberry transplants in plant factories with artificial lighting (PFALs). However, the impact of full-spectrum LEDs with varying red-to-blue ratios on the growth and biomass accumulation of strawberry transplants remains inadequately explored. Moreover, the influence of the strawberry transplants obtained on runner plant propagation in greenhouses post-transplanting is unclear. For this reason, this study utilized full-spectrum LEDs (white LEDs and white and red LEDs) with red-to-blue ratios of 0.9 (W0.9), 1.5 (WR1.5), 2.0 (W2.0), and 2.9 (WR2.9) for producing strawberry transplants in the PFAL over a period of 39 d. Subsequently, ten randomly selected transplants from each above treatment were planted as mother plants in a Chinese solar greenhouse for runner plant propagation, continuing for 98 d. These treatments were named as M-W0.9, M-WR1.5, M-W2.0, and M-WR2.9, respectively. Results indicated that the total leaf area of transplants in W2.0 was 1.2 times greater than those in W0.9 and WR2.9, exceeding 300 cm². Conversely, the net photosynthetic rate and Fv/Fm of strawberry transplant leaves were significantly higher in W0.9 compared with other treatments, declining with increasing red-to-blue ratio. In terms of biomass and morphological attributes, transplants in W2.0 exhibited higher fresh mass (17.2 g), leaf count (7 per plant), crown diameter (9.9 mm), and crown dry mass (0.27 g) than other treatments. Therefore, the strawberry transplant quality in W2.0 was significantly better than that of the other treatments. Moreover, shoot dry mass of strawberry mother plants in M-W2.0 was 1.4 and 1.3 times greater than those in M-W0.9 and M-WR2.9, respectively. The number of total runner plants and three-leafed runner plants produced in M-W2.0 were 1.9 times higher than those in M-W0.9, averaging 21 and 18 per plant, respectively. And mother plants in M-W2.0 produced 7 runners per plant, resulting in increased runner plant numbers. In conclusion, full-spectrum LEDs with a red-to-blue ratio of 2.0 enhanced the quality of strawberry transplants and significantly promoted runner plant propagation in greenhouses post-transplanting, and can be recommended as effective light sources for strawberry transplant production in PFALs. Key words: strawberry; LED light quality; transplant quality; runner plant propagationDOI: 10.25165/j.ijabe.20251802.9265Citation: Chen J, Ji F, Gao R W, He D X. Enhancing transplant quality by optimizing LED light spectrum to advance posttransplant runner plant propagation in strawberry. Int J Agric & Biol Eng, 2025; 18(2): 55–62.